Pengembangan Kurikulum Pendidikan Anak Usia Dini Berbasis Karakter - Fitria, Rosda Ayu; Aulia, Rifqi (Musamus Journal of Primary Education, 2021)
Character education at AUD is the basis that must be applied, given the increasingly complex world of children, as well as so diverse information and communication, which have an impact on children. In the application of character education, of course, it will not be separated from the arrangement of the curriculum that will make it easier for educators to achieve an educational goal. This research aims to describe the development of a character-based early childhood curriculum. This research uses a qualitative approach that is literature study. The data analysis technique used in this research is content analysis which is an in-depth discussion of the content of information obtained through reference books and journals. The result of this research is that with the development of an appropriate curriculum, learning will run according to the expected goals. Planning must be made every time learning, without planning, learning will not go well and directed. Likewise, when applying character values, some preparation is needed by each class teacher. As well as character planting, it is not only limited to the curriculum, but can run effectively when this character cultivation is carried out in the daily habits of children, by this the children can improve the character development in themselves.